Sistem Pendukung Keputusan Pemberian Bonus Kepada Karyawan Berbasis Web - Jolie Felicia; Hugeng; Tri Sutrisno (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
Employees are a company resource to produce services or goods to meet consumer needs. To improve the performance of company resources, companies need to meet the needs of employees and give appreciation to employees who have good performance, one of which is giving bonuses. PT Fiture Teknologi Inovasi is a company engaged in the field of IT solutions. Determining bonuses still uses manual methods and there is no media or tools that can process employee ratings who deserve bonuses. Based on the problems above, the authors made a decision to support a web-based bonus system using the weighted product and weighted sum methods. The result of this system is one employee who has the highest vector v value of the two methods. From the results of the calculation of the data, then the percentage of the method's suitability with the data is calculated.